THE DEVELOPMENT OF A ROBUST RISK MANAGEMENT PLAN FOR THE CONTINUOUS SUPPLY OF WATER TO HOSPITALS IN THE WESTERN CAPE PROVINCE - Bezuidenhout, Saija; Dippenaar, Amey (The South African Journal of Industrial Engineering, 2019)
The objective of this research is to develop a robust water supply risk management and response plan for Somerset Hospital thatreflects the institution’s specific requirements, and to preparegeneral guidelines for the Western Cape Government Health Department in order to assist in developing risk management and response plans for all of its health care facilities. This will enable the Western Cape Government Health Department to be resilient in withstanding gradual systemic shocks and major crises in the supply of water to hospitals. The methodology is based on ISO 31000:2009, but it extends the approach using historical evaluations and a business impact analysis. Through the research it has become evident that one public sector in South Africa still lacks proper risk management planning, and that, on the whole, there is a global void in research into water resilience, especially that focusing on health care facilities.